Ответ:
Объяснение:
у=[tex]\frac{168x}{x^{2} } -2x[/tex]=[tex]\frac{168}{x}-2x=\frac{168-2x^{2} }{x}[/tex]
6.1) [tex]2x^{2} -5x-18=0[/tex] D=25+144=169 ⇒[tex]x_{1} =\frac{5+13}{4} =4,5\\x_{2}=\frac{5-13}{4}=-2[/tex]
2)[tex]\frac{x^{2} }{x-2} -\frac{5x-6}{x-2}=0[/tex]⇒[tex]\frac{x^{2}-5x+6 }{x-2}=0[/tex]⇒[tex]\frac{(x-2)(x-3)}{x-2}=0[/tex]⇒x-3=0⇒x=3
uploaded
savea
spng (1).png
saveaspng (1).png
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
у=[tex]\frac{168x}{x^{2} } -2x[/tex]=[tex]\frac{168}{x}-2x=\frac{168-2x^{2} }{x}[/tex]
6.1) [tex]2x^{2} -5x-18=0[/tex] D=25+144=169 ⇒[tex]x_{1} =\frac{5+13}{4} =4,5\\x_{2}=\frac{5-13}{4}=-2[/tex]
2)[tex]\frac{x^{2} }{x-2} -\frac{5x-6}{x-2}=0[/tex]⇒[tex]\frac{x^{2}-5x+6 }{x-2}=0[/tex]⇒[tex]\frac{(x-2)(x-3)}{x-2}=0[/tex]⇒x-3=0⇒x=3
uploaded
savea
spng (1).png
saveaspng (1).png